Aku Bersyukur, Aku Bahagia: Program Intervensi Psikologi Positif Berbasis Experiential Learning Untuk Meningkatkan Kebersyukuran Pada Siswa Sekolah Dasar - Fahwan Aldi Pratama; Farah Syahla Dzahabiyah; Najwa Salvabillah Putri Rahdiansyah; Samuel Naufal Rahmat Yefta Tuwaidan; Lenny Utami Afriyenti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Gratitude is a positive character strength that plays an important role in children's social, emotional, and psychological development. However, cultivating gratitude cannot be achieved solely through lectures or advice. This study aimed to examine the effectiveness of an Experiential Learning–based positive psychology intervention program entitled "I Am Grateful, I Am Happy" in enhancing gratitude among elementary school students. The program was implemented with five elementary school students through four sessions designed according to Kolb's four stages of Experiential Learning: Concrete Experience, Reflective Observation, Abstract Conceptualization, and Active Experimentation. Data were collected through observations, brief interviews, and pre-test and post-test assessments using gratitude and experiential learning scales. The data were analyzed using a paired-samples t-test. The results indicated a significant increase in both gratitude scores (p = .017, two-tailed) and experiential learning scores (p .001, two-tailed) after participation in the program. These findings suggest that an experiential learning–based intervention is effective in fostering gratitude among elementary school children and may serve as an alternative approach for promoting positive character development in children.